HIV status disclosure and associated outcomes among pregnant women enrolled in antiretroviral therapy in Uganda: a mixed methods study - Naigino, Rose; Makumbi, Fredrick; Mukose, Aggrey; Buregyeya, Esther; Arinaitwe, Jim; Musinguzi, Joshua; Wanyenze, Rhoda K. (Reproductive health, 2017)
Disclosure of HIV positive status to sexual partners is promoted by HIV prevention programs including those targeting the prevention of mother-to-child transmission. Among other benefits, disclosure may enhance spousal support and reduce stigma, violence and discrimination. HIV status disclosure and associated outcomes were assessed among a cohort of women, newly initiating lifelong antiretroviral therapy in Uganda between October 2013 and May 2014. Methods: This was a mixed method study, drawing data froma prospective cohort study of 507 HIV positive pregnant women on lifelong antiretroviral therapy, who were followed for four months to determine disclosure and itsoutcomes. Women were recruited from three facilities for the cohort study; in addition, fifty-seven women were recruited to participate in qualitative interviews from six facilities. Factors associated with spousal support and negative outcomes were determined using random-effects logistic regression in two separate models, with prevalence ratio as measure of association. In-depth interviews were used to document experiences with disclosure of HIV status. Results: Overall HIV status disclosure to at least one person was high [(375/507), 83.7%]. Nearly three-quarters [(285/389), 73.3%], had disclosed to their spouse by the fourth month of follow up post-enrolment. Among married women,spousal supportwas high at the first 330/407 (81.1%) and second follow-up 320/389 (82.2%). The majority of women who reported spousal support for either antenatal care or HIV-related care services had disclosed their HIV status totheir spouses (adj.PR = 1.17; 95% CI: 1.02–1.34). However, no significant differences were observed in the proportion of self-reported negative outcomes by HIV status disclosure (adj.PR = 0.89; 95% CI: 0.56–1.42). Qualitative findings highlighted stigma and fear of negative outcomes as the major barriers to disclosure. Conclusion: HIV status disclosure to partners by pregnant women on lifelong antiretroviral therapy was associated with increased spousal support, but was impeded by fear of adverse outcomes such as stigma, discrimination and violence. Interventions to reduce negative outcomes could enhance HIV status disclosure.
Keywords: HIV status disclosure; Spousal support; Stigma; Discrimination